2020
DOI: 10.1021/acsami.0c13693
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Performance of Sr0.9La0.1TiO3-Based Ceramics Regulated by Nanostructures

Abstract: La-doped strontium titanite (Sr 0.9 La 0.1 TiO 3 ) is a promising candidate for n-type oxide thermoelectric materials. However, the ZT values of this material are low, leading to low conversion efficiency. Improvements in this efficiency are required. In this work, a high ZT value of 0.50 was obtained for Sr 0.9 La 0.1 TiO 3 ceramic samples by adding 10 wt % Bi 2 O 3 sintering aids and 20 wt % nanosized Ti powders to the matrix material. Although Ti was oxidized to TiO 2 during the sintering process, nanoscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…By processing under reducing conditions a high PF, comparable with that of Bi 2 Te 3 can be achieved, but reducing thermal conductivity is much more of a challenge as nanostructuring is less effective than in many other materials. Doping on the cation A site, with La in place of ∼10% of the Sr has been popular and effective, which under reducing conditions leads to the formation of oxygen vacancies, which enhance electrical conductivity and reduce thermal conductivity [596][597][598][599][600][601][602][603][604][605][606][607][608][609][610][611][612]. On the cation B site, doping with higher valent Nb leads to metallic conduction and simultaneously increases S because the effective mass m * is increased; consequently, the PF σS 2 is enhanced, with values of ∼1500 µW m −1 K −2 at 1000 K recorded for SrTi 0.8 Nb 0.2 O 3 epitaxial films and a zT max of 0.37 [596].…”
Section: Oxide Thermoelectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…By processing under reducing conditions a high PF, comparable with that of Bi 2 Te 3 can be achieved, but reducing thermal conductivity is much more of a challenge as nanostructuring is less effective than in many other materials. Doping on the cation A site, with La in place of ∼10% of the Sr has been popular and effective, which under reducing conditions leads to the formation of oxygen vacancies, which enhance electrical conductivity and reduce thermal conductivity [596][597][598][599][600][601][602][603][604][605][606][607][608][609][610][611][612]. On the cation B site, doping with higher valent Nb leads to metallic conduction and simultaneously increases S because the effective mass m * is increased; consequently, the PF σS 2 is enhanced, with values of ∼1500 µW m −1 K −2 at 1000 K recorded for SrTi 0.8 Nb 0.2 O 3 epitaxial films and a zT max of 0.37 [596].…”
Section: Oxide Thermoelectricsmentioning
confidence: 99%
“…By optimized doping of A and or B sites of STO, zT max values at high temperatures have remained stubbornly around 0.38 [597-599, 603, 604, 610]. There have been isolated reports of zT max values above 0.5 for STO-based materials [602,608,611], but an interesting development in recent years has been the enhancement of transport properties at lower temperatures through additions of carbon-based species. Lin et al [600] showed that incorporation of small amounts of graphene (<1 wt%) into STO enabled single crystal-like electronic transport behavior, with high electrical conductivity at temperatures of 373 K or less.…”
Section: Oxide Thermoelectricsmentioning
confidence: 99%
“…Therefore, it is urgent to seek material with both low thermal conductivity and large Seebeck coefficient simultaneously. The summarization of thermal conductivity and Seebeck coefficient of SrTiO 3 ‐based thermoelectric materials is shown in Figure 7(f), including Sr 0.9 La 0.1 (Zr 0.25 Sn 0.25 Ti 0.25 Hf 0.25 )O 3 , [100] La 0.1 Dy 0.1 Sr x TiO 3 , [108] Ag‐SrTiO 3 , [109] La−Nb co‐doped SrTiO 3 , [94] Nb‐doped SrTiO 3 , [110] La−Dy‐Nb co‐doped SrTiO 3 , [111] La‐doped SrTiO 3 , [112] Ta‐substituted SrTiO 3 , [113] RGO‐SrTiO 3 , [114] Ti‐Sr 0.9 La 0.1 TiO 3 , [115] and Sr(Ti 0.2 Fe 0.2 Mo 0.2 Nb 0.2 Cr 0.2 )O 3 [99] …”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Thermoelectric (TE) materials can realize the mutual conversion of thermal and electrical energy, thus providing an innovative technique to reduce the power consumption. Additionally, TE devices have the benefits of no moving parts, no noise, and precision in temperature management, rendering them valuable for cooling and power generation. The TE efficiency is determined by the dimensionless figure of merit ZT = α 2 σ T/ κ, where α, σ, κ, and T denote the Seebeck coefficient, the electrical conductivity, the total thermal conductivity, and the absolute temperature, respectively. Generally, a larger power factor ( PF = α 2 σ) and a lower κ can achieve a higher ZT . In the recent two decades, various tactics have been implemented to modify the crystalline phases of TE materials to reduce their thermal conductivity while maintaining their high PF , such as nanostructuring, solid-solution alloying, defect engineering, and introducing multiscale defect centers. A radically different approach may be undertaken depending on the materials with intrinsically low κ, making the PF the parameter to be improved. …”
Section: Introductionmentioning
confidence: 99%